Investigation of the mechanisms of action behind Electromotive Drug Administration (EMDA) - Kos, Bor (PeerJ, 2016)
OBJECTIVE: Bladder cancer is a cause of considerable morbidity worldwide. Electromotive Drug Administration is a method that combines intravesical chemotherapy with local electric field application. Electroporation has been suggested among other mechanisms as having a possible role in the therapy, so the goal of the present study was to investigate the electric fields present in the bladder wall during the treatment to determine which mechanisms might be involved. MATERIAL AND METHODS: Electromotive Drug Administration involves applying intravesical mitomycin C with direct current of 20 mA delivered through a catheter electrode for 30 min. For numerical electric field computation we built a 3-D nonhomogeneous patient specific model based on CT images and used finite element method simulations to determine the electric fields in the whole body. RESULTS: Results indicate that highest electric field in the bladder wall was 37.7 V/m. The mean electric field magnitude in the bladder wall was 3.03 V/m. The mean magnitude of the current density in the bladder wall was 0.61 A/m(2). CONCLUSIONS: The present study shows that electroporation is not the mechanism of action in EMDA. A more likely explanation of the mechanism of action is iontophoretic forces increasing the mitomycin C concentration in the bladder wall.